Association between neighborhood deprivation and type 2 diabetes risks among asthma patients: a nationwide population-based cohort study - Yuwen Wang; Yuhong Zhang; Kristina Sundquist; Jan Sundquist; Huifang Yang; Xinjun Li (Scientific Reports)
Abstract This study aimed to investigate the potential impact of neighborhood deprivation on the incidence of type 2 diabetes mellitus (T2DM) among individuals with asthma. This nationwide, open cohort study conducted in Sweden from 1997 to 2018 included asthma patients of all ages (n = 1,051,240) to assess their subsequent risk of developing T2DM. The study compared asthma patients residing in highly deprived neighborhoods with those living in moderately or less deprived areas (reference group). Cox proportional hazards regression models were employed to analyze the association between neighborhood deprivation and T2DM incidence, with results expressed as hazard ratios (HRs) and 95% confidence intervals (95% CIs). Analyses were stratified by sex and adjusted for potential confounders. A significant association between neighborhood deprivation and T2DM risk in asthma patients was shown. These associations remained statistically significant after adjusting for confounders, with adjusted HRs of 1.44 (95% CI 1.38–1.50) for men and 1.51 (95% CI 1.46–1.57) for women. Furthermore, a graded relationship was observed, with higher levels of neighborhood deprivation associated with an increased incidence of T2DM among asthma patients. These findings underscore critical clinical and public health concerns. The results of this study provide valuable insights for policymakers, highlighting the need to consider neighborhood deprivation when allocating resources in primary healthcare settings. They also offer guidance for optimizing clinical care strategies for patients in socioeconomically disadvantaged communities.